Numerical simulation of pressure drop for three-dimensional rectangular microchannels. Issue 6 (6th August 2018) - Duan, Zhipeng; Liang, Peng; Ma, Hao; Ma, Niya; He, Boshu
Abstract : Purpose: The purpose of this paper is to numerically investigate the flow characteristics and extend the data of friction factor and Reynolds number product of hydrodynamically developing laminar flow in three-dimensional rectangular microchannels with different aspect ratios. Design/methodology/approach: Using a finite-volume approach, the friction factor characteristics of Newtonian fluid in three-dimensional rectangular ducts with aspect ratios from 0.1 to 1 are conducted numerically under no-slip boundary conditions. A simple model that approximately predicts the apparent friction factor and Reynolds number product f app Re is referenced as a semi-theoretical fundamental analysis for numerical simulations. Findings: The accurate and reliable results of f app Re are obtained, which are compared with classic numerical data and experimental data, and the simple semi-theoretical model used and all comparisons show good agreement. Among them, the maximum relative error with the classic numerical data is less than 3.9 per cent. The data of f app Re are significantly extended to other different aspect ratios and the novel values of f app Re are presented in the tables. The characteristics of f app Re are analyzed as a function of a non-dimensional axial distance and the aspect ratios. A more effective and accurate fourth-order fitting equation for the Hagenbach's factor of rectangular channels is proposed. Originality/value: From the reliable data, it is shown that the values of f app Re and the model can be references of pressure drop and friction factor for developing laminar flow in rectangular channels for researchers and engineering applications.